Dampak Perilaku Phubbing: Literatur Review - Farkhah, Laeli; Maretyara Saptyani, Putri; Ikhda Syamsiah, Resti; Ginanjar. T, Heru (Jurnal Keperawatan Komplementer Holistic, 2023)
In the current digital era, almost all human activities involve technology, one of which is a smartphone. This is proven based on smartphone user data in Indonesia as much as 89.63% in 2021 and smartphone usage 3-4 hours, 5-6 hours, and more than 7 hours a day. This phubbing phenomenon has negative impacts that need to be watched out for in various age ranges, from children to the elderly. This condition requires attention and anticipation from a health perspective in order to ensure the quality of human life. The purpose of this literature study is to identify early on the various impacts of phubbing behavior so that it is beneficial for all individuals to stay healthy including biopsychosocial, cultural and spiritual. The method used in writing this literature study was an internet search of the Scopus, Science Direct, Proquest, Ebsco, Pubmed, Cochrane library, Willey Online Library, DOAJ, Google Scholar databases from 2012-2023 with the keywords phubbing, phubbing behavior, phubbing impact , phubbing effect, phubbing implication, negative effect of phubbing. The impact of phubbing behavior can be classified into 3 categories including physical, psychological/mental, and social health impacts.